A Analisis Kebutuhan Pengembangan E-booklet Interaktif Bernuansa Pembelajaran Mendalam (Deep Learning) pada Materi Keanekaragaman Hayati SMA: The - Arif Fikiansah; Lufri Lufri (LP2M UIN Ambon, 2026)
Teaching materials are an important aspect that serves as a learning resource for educators and students. The purpose of this study is to describe the results of the analysis of the need to develop an interactive e-booklet with a deep learning nuance on the biodiversity material of class X Phase E at SMA Negeri 3 Mukomuko. The research data used instruments for a preliminary study consisting of a biology teacher interview guide sheet and a student observation questionnaire. Then 1 biology teacher and 30 students became the objects of research. The data obtained in the preliminary study were analyzed using qualitative descriptive statistics to determine the need to develop an interactive e-booklet with a deep learning nuance on the biodiversity material of high school. The results of the student analysis stated that 96.7% agreed with the development of teaching materials in the form of an e-booklet. The conclusion of this study is that the development of an interactive e-booklet with a deep learning nuance can be one of the solutions to the problems faced by teachers and students, especially on the biodiversity material of SMA Phase E.